The Impact of Sustainability Reporting on Financial Performance of Listed Conglomerates in Nigeria - Musa, Nura; Lawal, Sagir; Idris, Hauwa Ibrahim (CV Media Inti Teknologi, 2025)
Background of study: Sustainability reporting has become vital in enhancing corporate transparency and accountability, especially in emerging economies such as Nigeria. Conglomerate firms, with diverse business portfolios, face increasing pressure to disclose non-financial information that reflects their environmental, social, and governance (ESG) commitments. Aims and scope of paper: This paper examines the impact of sustainability reporting on the financial performance of listed conglomerates in Nigeria. It specifically evaluates four dimensions of disclosure—environmental (ENV), economic (ECO), social (SOC), and governance (GOV)—and their effects on firms’ profitability measured by return on assets (ROA). The study covers six listed conglomerates on t he Nigerian Exchange (NGX) for the period 2015–2024. Methods: A quantitative research approach was applied using secondary data extracted from annual and sustainability reports. Panel data techniques, including fixed and random effects regressions with robust standard errors, were employed to analyze 60 firm-year observations. Leverage (LEV) was used as a control variable, and diagnostic tests for multicollinearity and heteroskedasticity ensured model validity. Result: The findings indicate that governance disclosure (GOV) significantly and positively influences ROA, while environmental disclosure (ENV) shows a small but positive association. Economic disclosure (ECO) has no significant effect, and social disclosure (SOC) displays a weak negative relationship with financial performance. Conclusion: The study concludes that governance and environmental transparency enhance financial outcomes among Nigerian conglomerates. Managers should strengthen sustainability governance structures, and regulators should promote consistent disclosure standards to support sustainable business performance.